2015
DOI: 10.1007/s12032-015-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase II dose-finding study of balugrastim in breast cancer patients receiving myelosuppressive chemotherapy

Abstract: Balugrastim is a once-per-cycle, fixed-dose recombinant protein comprising human serum albumin and granulocyte colony-stimulating factor under development for prevention of severe neutropenia in cancer patients receiving myelosuppressive chemotherapy. This phase II, multicenter, active-controlled, dose-finding pilot study evaluated balugrastim safety and efficacy versus pegfilgrastim in breast cancer patients scheduled to receive myelosuppressive chemotherapy and investigated two doses with similar efficacy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 14 publications
0
28
1
Order By: Relevance
“…These molecular changes may have affected receptor‐binding ability and our ability to distinguish between the efficacy of the reference pegfilgrastim and the biosimilars. The second hypothesis is that the subjects of the present study are different from the subjects of previous studies 23‐25 . The median age of patients was 49.9‐53.4 years in previous studies; however, it was 63 years (range: 26‐92 years) in the present study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…These molecular changes may have affected receptor‐binding ability and our ability to distinguish between the efficacy of the reference pegfilgrastim and the biosimilars. The second hypothesis is that the subjects of the present study are different from the subjects of previous studies 23‐25 . The median age of patients was 49.9‐53.4 years in previous studies; however, it was 63 years (range: 26‐92 years) in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…To date, published studies have shown no difference in efficacy and safety between reference pegfilgrastim and its biosimilars 15 . However, there is not enough evidence to draw a definitive conclusion because the number of studies is small; most of these studies were conducted in patients with breast cancer, and the interpretation of efficacy was mainly focused on the duration of neutropenia 23‐25 . In this study, the biosimilars were associated with a higher incidence of neutropenia and febrile neutropenia than the reference pegfilgrastim, especially in the first cycle of R‐CHOP chemotherapy.…”
Section: Discussionmentioning
confidence: 70%
“…The 40-and 50-mg-balugrastim doses were selected for evaluation based on a phase II, sequential dose-escalation pilot study of once-per-cycle 30, 40, and 50 mg of balugrastim versus 6 mg of pegfilgrastim in breast cancer patients receiving chemotherapy with doxorubicin and docetaxel [21].The phase II study suggested that, compared with pegfilgrastim, 40 and 50 mg of balugrastim provided similarly effective prophylactic neutrophil support in breast cancer patients receiving myelosuppressive chemotherapy. These findings were confirmed in the current phase III study.…”
Section: Discussionmentioning
confidence: 99%
“…This phase III noninferiority study aimed to evaluate the efficacy and safety of 40-and 50-mg doses of balugrastim versus a 6-mg dose of pegfilgrastim (Neulasta; Amgen Inc., Thousand Oaks, CA, http://www.amgen.com) for the prophylaxis of chemotherapy-induced neutropenia.The doses in the current study were chosen based on the results of a doseescalation phase II study that demonstrated similar safety and efficacy between the 40-and 50-mg doses of balugrastim and the active comparator, pegfilgrastim [21].…”
Section: Introductionmentioning
confidence: 99%
“…Neutropenia and febrile neutropenia (FN) represent two frequent complications of chemotherapy treatments. 1 Neutropenia can be defined as a reduction in the normal count of neutrophils, while FN represents a medical emergency in which the absolute neutrophils count (ANC) falls below the value of 0.5×10 9 /L and the body temperature is equal or superior to 38°C for >1 hour. 2 Neutrophils act as early responders against pathogens.…”
Section: Introduction To Balugrastim and Management Issues In Chemothmentioning
confidence: 99%